Evaluation of creep strain concrete specimens subjected to stress reversal - York, Harrison (My University, 2025)
In the repair and rehabilitation of concrete structures, it is important to know how concrete could behave in different scenarios. In some cases, such as in prestressed bridges or prestressed concrete containment vessels, structures may be exposed to a stress that is outside of the designed use for that structure. The purpose of this research is to understand how creep affects the flexural response of concrete given a sudden stress reversal. A series of normal strength 4"x4"x36" concrete beams were cast and tested for this research. The specimens were loaded axially at 30%f'c and 50%f'c for 70-days and then subjected to a four point loading flexural test. Brass inserts were cast into the beam so that a Whittemore gauge could be used to measure the creep during the axially loading phase and later a surface mounted strain gauge was used to measure the creep recovery at unloading and the strain experienced during the flexural test. From these tests it was discovered that beams that have experienced more creep have a similar but slightly lower flexural strength and a lower flexural modulus of elasticity. It was also found that after specimens have undergone creep, a one-month relaxation period lessened the reduction in strength and stiffness.
Keywords: Concrete; Creep; Stress reversal